GABA and glutamate associate with evidence of preclinical Alzheimer disease in humans: A 7 Tesla MRSI and 11C‐PIB PET study: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Schreiner, Simon J.; Kirchner, Thomas; Van Bergen, Jiri M.G.; Wyss, Michael; Steininger, Stephanie C.; Gietl, Anton F.; Buck, Alfred; Treyer, Valerie; Nitsch, Roger M.; Pruessmann, Klaas P.; Hock, Christoph; Henning, Anke; et al.
Abstract: Background: Early stage Alzheimer disease (AD) is characterized by brain change that includes altered neuronal inhibition and excitation. However, only few data is available for clinical populations. Here, we tested the hypothesis that GABA and glutamate (Glu), the major inhibitory and excitatory neurotransmitters, associate with changes in episodic memory performance, beta‐amyloid (Aß) burden, and genetic risk of AD in old‐aged adults with normal cognition. Method: Thirty old‐aged adults underwent genotyping of the apolipoprotein E epsilon 4 allele (APOE4), MRI and MRSI at 7 Tesla (7T) for estimating GABA and Glu levels (referenced to creatine) in grey and white matter of the posterior cingulate and precuneus region, positron emission tomography with 11 C‐Pittsburgh compound‐B for measuring Aß burden, and cognitive testing at two time points for assessing longitudinal change in verbal episodic memory performance. Result: Higher levels of GABA and Glu were associated with higher Aß burden (GABA: ß=0.59; p=0.005; R 2 =0.41; Glu: ß=0.57; p=0.006; R 2 =0.30), which was particularly evident in APOE4 carriers (significant interaction of Aß burden and APOE4; GABA: ß=0.93; p<0.001; R 2 =0.80; Glu: ß=0.81; p<0.001; R 2 =0.59). GABA classified subjects with high vs. low PiB‐SUVR with good accuracy (AUC=0.77; Figure 1). APOE4 and high Aß burden were associated with declining performance at the Verbal Learning and Memory Test (VLMT), immediate recall. However, these associations were attenuated by GABA and Glu, which both associated with VLMT decline (GABA: ß= ‐0.48; p=0.015; R 2 =0.18; Glu: ß= ‐0.41; p=0.024; R 2 =0.15; Figure 2). These associations, however, did not survive adjustment for age, sex and education. All findings were exclusively observable for grey and not white matter levels of GABA and Glu. Conclusion: Our findings may provide clinical evidence of higher inhibitory and excitatory capacity associated with episodic memory decline, genetic risk and pathology of AD.